Problematika Pertimbangan Hukum Hakim Dalam Putusan MK Nomor 66/PUU-XXIV/2026 Terkait Kerugian Keuangan Negara Dalam Hukum Administrasi Negara - Reva Aurelia Azzah; Ahnaf Daffa Fakhruddin Madjid; Muh. Ali Masnun (Universitas Negeri Surabaya, 2026)
This research focuses on the legal considerations of judges in the Constitutional Court Decision Number 66/PUU-XXIV/2026 regarding the interpretation of state financial losses from the perspective of Administrative Law. The research problem arises from the conceptual differences between state financial losses in criminal law, which emphasize tangible, actual, and financially calculable losses, and the concept of state financial losses in Administrative Law, which has a broader scope. This research uses a normative legal research method with a statutory approach, a conceptual approach, and a case approach thru the analysis of Constitutional Court Decision Number 66/PUU-XXIV/2026. The research results show that the Constitutional Court maintains the use of the term